2010
DOI: 10.1007/s00438-010-0570-3
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a high-density composite map and comparative mapping of segregation distortion regions in barley

Abstract: Segregation distortion can negatively impact on gains expected using selection. In order to increase our understanding of genetic factors that may influence the extent and direction of segregation distortion, segregation distortion analyses were conducted in four different doubled haploid (DH) populations. A high-density composite map of barley was then constructed by integrating information from the four populations. The composite map contained 2,111 unique loci, comprising RFLP, SSR and DArT markers and span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 108 publications
4
55
0
Order By: Relevance
“…The mapped skewed loci appeared to locate together as segregation distortion regions in the genetic map, as previously reported in L. edodes (Terashima et al 2002), P. pulmonarius (Okuda et al 2009) and P. eryngii (Okuda et al 2012). The cluster distribution of skewed loci seemed to indicate that the segregation distortion of markers is most likely caused by genetic factors rather than statistical bias (Li et al 2010).…”
Section: Molecular Markers Used In This Studysupporting
confidence: 75%
“…The mapped skewed loci appeared to locate together as segregation distortion regions in the genetic map, as previously reported in L. edodes (Terashima et al 2002), P. pulmonarius (Okuda et al 2009) and P. eryngii (Okuda et al 2012). The cluster distribution of skewed loci seemed to indicate that the segregation distortion of markers is most likely caused by genetic factors rather than statistical bias (Li et al 2010).…”
Section: Molecular Markers Used In This Studysupporting
confidence: 75%
“…The reason for the skewed segregation in our study is unclear. Segregation distortion is a common phenomenon in many plants and is recognized as a potentially powerful evolutionary force (Li et al, 2010;Li et al, 2015); however, its underlying mechanism is not understood (Cai et al, 2015). Suggested causes include aneuploidy, chromosomal translocation, competition among gametes, and the inheritance of alleles affecting the viability of the zygote, embryo, or seedling (Lashermes et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Segregation distortion, also called "meiotic drive," may be caused by genetic elements, including gametic selection (pollen tube competition, lethal pollen, and preferential fertilization), zygotic selection, interspecific sterility genes (S), and chromosome translocation (Lyttle 1991;Kumar et al 2007;Gutiérrez et al 2010;Liu et al 2010). It has been suggested that meiotic drive elements are highly important for the evolution of recombination and sexual reproduction (Hurst and Werren 2001;Jaenike 2001;Li et al 2010).…”
Section: Molecular Mapping Of Rfmentioning
confidence: 99%
“…Segregation distortion, also called "meiotic drive," may be caused by genetic elements, including gametic selection (pollen tube competition, lethal pollen, and preferential fertilization), zygotic selection, interspecific sterility genes (S), and chromosome translocation (Lyttle 1991;Kumar et al 2007;Gutiérrez et al 2010;Liu et al 2010). It has been suggested that meiotic drive elements are highly important for the evolution of recombination and sexual reproduction (Hurst and Werren 2001;Jaenike 2001;Li et al 2010).Segregation distortion has been reported for sunflower populations derived from the interspecific crosses involving wild species in the mapping of a downy mildew resistance gene on LG 1, Pl ARG , which originated from H. argophyllus Torrey and Gray (Dußle et al 2004;Wieckhorst et al 2010). Significant segregation distortion of the codominant markers closely linked to the Pl ARG gene was observed in the F 2 Figure 4 Representative results of the markers amplified by the ORS433 primer pair among the four bulks and the individuals constituting each bulk, respectively, on a nondenaturing polyacrylamide gel.…”
mentioning
confidence: 99%